Pengaruh Penggunaan Media Big Book Writing Terhadap Kemampuan Menulis - Tilmasani Tilmasani (Jurnal MUDARRISUNA: Media Kajian Pendidikan Agama Islam, 2022)
Briefly, these four competencies can be explained as follows: Pedagogic competence is the ability to process student learning which includes understanding of students, design and implementation learning, evaluating learning outcomes, and developing students to actualize its various potentials. Personal competence is a personality ability that is steady, stable, mature, wise, and authoritative, be a role model for students, and have a noble character. Competence Professional competence is the ability to master learning material widely and depth that allows it to guide students to meet the standard competencies set out in the National Education Standards. Competence Social education is the ability of educators as part of society to communicate and interact effectively with students, fellow educators, education staff, parents/guardians of students, and the surrounding community. Educational management is management applied in educational development. In a sense it is the art and science of managing Islamic education resources to achieve the goals of Islamic education effective and efficient. Talking about management issues, of course, can't be separated with four existing components, namely (POAC) planning, organizing, actuating and controlling. The views of experts conclude that management Islamic education according to the perspective (view) of the Qur'an is as follows: The following are flexible, effective, efficient, open, cooperative and participatory. The purpose of Islamic education management is that all resources, equipment, or the existing facilities within an organization can be moved in such a way as to avoid to a minimum maybe all the wastage of time, energy, material, and money to achieve predetermined organizational goals.